Optimization of the plasma electrolytic oxidation process parameters on 7075 aluminum alloy using Taguchi method - Erfan Pirhadi Nouri; Saeed Reza Allahkaram; Mehrnaz Gharagozlou (Journal of Materials Research and Technology)
In this study, the objective was to enhance the corrosion resistance of plasma electrolytic oxidation (PEO) coatings on AA7075 alloy by optimizing the PEO process parameters including current density, time, frequency, and duty cycle, using the Taguchi design of experiments method. The optimal values for these parameters were determined to be 40 A/dm2, 15 min, 1500 Hz, and 30 %, respectively. The influence of each parameter was also discussed, and it was found that the duty cycle was the most significant parameter influencing the corrosion resistance of the PEO coatings. The polarization resistance of the optimized coating reached 105.206 MΩ cm2, which was 49 times higher than the substrate. This improvement indicates an enhanced barrier effect against corrosive agents, suggesting the potential of the optimized PEO coating for use in demanding industrial environments such as aerospace and marine applications. The results of electrochemical impedance spectroscopy (EIS) also indicated an improvement in corrosion resistance. The microstructure and surface morphology of the optimized coating were examined using scanning electron microscopy (SEM) equipped with energy-dispersive X-ray spectroscopy (EDS), which revealed a typical structure of PEO coatings. The porosity of the coating was 3.95 % and the average diameter of micropores was 1.57 μm. The constituent elements of the coating were aluminum, oxygen, silicon, magnesium, and zinc. Additionally, the coating exhibited good adhesion to the substrate, and the thickness of the optimized coating was 9.4 μm. X-ray diffraction (XRD) analysis revealed that the main phases of the coating were gamma-alumina and magnesium oxide.